Educação e socialidade: o vínculo societal no clube de mães do bairro Jardim Seminário no município de Francisco Beltrão/PR - Marques, Maria Roziane Aparecida de Freitas (2021)
In this dissertation we analyze the cultural identity and the societal bond of a group of women from the Mothers' Club from Jardim Seminário neighborhood in the city of Francisco Beltrão, Paraná. For this investigation we defined the following question as a research problem: How is the societal bond built among the women who participate in the Mothers' Club in the Jardim Seminário neighborhood? We outlined as a general objective to know the process of identity affirmation and experience of a group of women who work at the Divino Mestre Mother’s Club in the Jardim Seminário neighborhood. The specific objectives established were: a) to identify how the cultural identity affirmation of a group of women occurs, in the context of the Jardim Seminário neighborhood; b) to understand the meaning of "being a woman" for the research subjects; c) to analyze the cultural markers responsible for the maintenance of the societal bond among the women of the group studied. The research is outlined as qualitative research with an ethnographic approach and the instruments we used to collect information were: narrative interviews and transcriptions; Field Diary; Photographic record (from the collection of the women from the Mothers' Club and those produced by the observation and description of the Jardim Seminário neighborhood; document analysis (minutes, newspapers and other relevant documents for information collection). To understand the existing societal bond in the group, we established the following categories: cultural pluralities, the societal and emotional bond, conviviality, religiosity, as significant markers to understand the identification and forms of rooting in the space of sociality. (To give theoretical and methodological support to the actions we used the contributions Certeau (2013), Hall (2009, 2015), Maffesoli (1998, 2001, 2006), Marques (2008), Silva (2009), among others. Contact with the locus of the dissertation with the intention of research began in 2017 and 2018. The material collected and analyzed indicated that the group of women in their coexistence in the Divino Mestre Mother’s Club, locus of the research, use cultural markers to promote the continuation of the societal bond:religiosity (as a reconnection), basic sociality, being together as a relationships structuring, the importance of gift and counter gift in the practices of daily life. The mothers' club is capable of transforming the meeting place of apprehension of the organic connection in which presences become a possibility of healing, of encounter, and of endurance.